2012
DOI: 10.3762/bjoc.8.6
|View full text |Cite
|
Sign up to set email alerts
|

A general and facile one-pot process of isothiocyanates from amines under aqueous conditions

Abstract: SummaryA general and facile one-pot protocol for the preparation of a broad range of alkyl and aryl isothiocyanates has been developed from their corresponding primary amines under aqueous conditions. This synthetic process involves an in situ generation of a dithiocarbamate salt from the amine substrate by reacting with CS2 followed by elimination to form the isothiocyanate product with cyanuric acid as the desulfurylation reagent. The choice of solvent is of decisive importance for the successful formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 62 publications
2
41
0
Order By: Relevance
“…Pyrrolidine and its derivatives are widely used in agrochemicals, photographic chemicals, corrosion inhibitors and used as curing agent for epoxyresins and acted as a catalyst in the manufacture of polyurethane [21][22][23][24]. Literature survey shows that, many biologically active alkaloids are possessing pyrrolidine ring system [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Pyrrolidine and its derivatives are widely used in agrochemicals, photographic chemicals, corrosion inhibitors and used as curing agent for epoxyresins and acted as a catalyst in the manufacture of polyurethane [21][22][23][24]. Literature survey shows that, many biologically active alkaloids are possessing pyrrolidine ring system [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome difficulties related to handling toxic and malodorous thiophosgene, there was decided to synthetize isothiocyanates 16a-c by the reaction of corresponding dithiocarbamates with thiophilic reagents, diacetoxyiodobenzene or cyanuric chloride. [17][18][19] Unfortunatelly, the preparation of dithiocarbamates by the reaction of amines 8a-c with carbon disulfide was not successful, probably due to low nucleophilicity of amines 8a-c. Therefore the thiophosgene-mediated formation of isothiocyanates had to be used (Scheme 10).…”
Section: Preparation Of Trisubstituted Acridinesmentioning
confidence: 99%
“…In the synthesis of thiourea, isothiocyanate is formed as a reactive intermediate and easily converted to other side product during isolation [2]. Many studies reported on the direct reaction of isothiocyanate intermediate with amines after isolation of KCl to produce thiourea in good purity [3].…”
Section: Introductionmentioning
confidence: 99%
“…It was due to the presence of more active sites of thiourea moieties containing C=S, C=O, and N-H groups, which are easily protonated under acidic condition and interacted with the carboxyl and phosphate groups of the bacterial surfaces, thus enhancing the biological activities [7]. Various methods have been reported to make this versatile group of thiourea derivatives easily accessible with excellent yields [2,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%